2020
DOI: 10.1002/isd2.12124
|View full text |Cite
|
Sign up to set email alerts
|

ICT4D 3.0? Part 1—The components of an emerging “digital‐for‐development” paradigm

Abstract: What has changed in the decade or so since the ideas of a new "ICT4D 2.0" phase were first mooted? This paper reviews those changes, based on a new framework model. At a foundational level, it looks at recent and current trends in digital technologies, data, processes and the implications these have for the user demographics and network structures that underpin the role of digital ICTs in international development. It then summarises some of the new building blocks of development: digital roles, digital produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…An earlier study by Tornatzky and Klien (1982) found a significant relationship between technology capability and an individual's TUB. Davide et al (2018) and Heeks (2020) found that if students feel that the technology helps them to perform their tasks better (perceived usefulness), they tend to develop positive TUB towards the technology. This is also confirmed in a study by Teeroovengadum et al (2017) which found that if a technology's use or functions are consistent with existing classroom practices, the university students will tend to develop positive TUB towards it.…”
Section: Job-fit and Continued Technology Usementioning
confidence: 99%
“…An earlier study by Tornatzky and Klien (1982) found a significant relationship between technology capability and an individual's TUB. Davide et al (2018) and Heeks (2020) found that if students feel that the technology helps them to perform their tasks better (perceived usefulness), they tend to develop positive TUB towards the technology. This is also confirmed in a study by Teeroovengadum et al (2017) which found that if a technology's use or functions are consistent with existing classroom practices, the university students will tend to develop positive TUB towards it.…”
Section: Job-fit and Continued Technology Usementioning
confidence: 99%
“…It subsequently came to mean innovating for productivity growth. A similar discourse has emerged in contemporary developing countries using digital technologies to accelerate formalization in order to achieve higher productivity and greater social and economic inclusion (Aker, 2011;Heeks, 2019;ITU, 2016;Singh, 2019). An important component of this strategy is to make the tax net fully inclusive, for instance by making value-added taxes digitally managed to increase compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Research in Information and Communication Technology for Development (ICT4D) has focused on diminishing the digital divide between high-income and low-and middle-income economies by exploring how information systems and technology can be utilized for the benefit of underprivileged communities (Ayanso et al, 2014). While progress is being made (Heeks, 2020;Walsham, 2017), there is an argument that ICT4D research also 'fails the poor' (Harris, 2015). While innovative e-learning solutions are emerging in remote and rural areas in developing countries, the sustainability of sometimes-disruptive innovations creates challenges for governments and policy makers (Badar, Mason, & Khan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, 79% of research adopted a quantitative method, 14% adopted a qualitative method, and only 7% adopted a mixed research method. Reflecting on the broad evolution of ICT4D discourse and the shifts in priorities articulated by UNESCO, some researchers (Heeks, 2020) also suggest the emergence of a new paradigm that repositions the term digital in development contexts.…”
Section: Introductionmentioning
confidence: 99%